KOBZAR’S “COSMO-PSYCHE-LOGOS” - Мафтин , Н. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is devoted to studying the problem of T. Shevchenko’s artistic thinking in the structure of elements modelling the world’s national image. It goes about the connection of Shevchenko’s word with fundamental archetypes, with such features of psychological composition of the national character as antaeusism, kordocentrism, theocentrism, as well as such ethic categories as Truth, Freedom, Love.